2009
DOI: 10.1002/glia.20903
|View full text |Cite
|
Sign up to set email alerts
|

Expression of antigen processing and presenting molecules by Schwann cells in inflammatory neuropathies

Abstract: Schwann cells are the myelinating glia cells of the peripheral nervous system (PNS) and can become targets of an autoimmune response in inflammatory neuropathies like the Guillain-Barré syndrome (GBS). Professional antigen presenting cells (APCs) are known to promote autoimmune responses in target tissues by presenting self-antigens. Other cell types could participate in local autoimmune responses by acting as nonprofessional APCs. Using a combined approach of immunocytochemistry, immunohistochemistry, and flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 62 publications
4
48
0
Order By: Relevance
“…This did not seem to be accompanied by an increase in DRG T‐cell number (Figure S6), indicating that any potential interactions are likely to affect the phenotype and activation state of T‐cells, rather than their abundance. This is in line with data from a related cell type: Horste et al have shown that Schwann cells in vitro express functional MHC I and II molecules which can activate T‐cells and hereby modulate the immune system (Meyer Zu Horste, Heidenreich, Lehmann, et al, ; Meyer Zu Horste, Heidenreich, Mausberg, et al, ). Our data indicate that SGCs might be able to modulate the immune system in a similar manner.…”
Section: Discussionsupporting
confidence: 85%
“…This did not seem to be accompanied by an increase in DRG T‐cell number (Figure S6), indicating that any potential interactions are likely to affect the phenotype and activation state of T‐cells, rather than their abundance. This is in line with data from a related cell type: Horste et al have shown that Schwann cells in vitro express functional MHC I and II molecules which can activate T‐cells and hereby modulate the immune system (Meyer Zu Horste, Heidenreich, Lehmann, et al, ; Meyer Zu Horste, Heidenreich, Mausberg, et al, ). Our data indicate that SGCs might be able to modulate the immune system in a similar manner.…”
Section: Discussionsupporting
confidence: 85%
“…[17]), and SCs most likely act as non-professional antigen-presenting cells under certain conditions. The IL-17-induced increased expression can be interpreted as an immunological alignment of SCs.…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin sections (10 µm) were stained with haematoxylin/eosin and an anti-CD68 (ED1, Serotec) or anti-MHC-II antibody (MCA2687R, Serotec) using DAB based staining as previously described [19]. The entire nerve cross section was photographed using a conventional microscope (Axioplan 2, Carl Zeiss) and the digital photographs were photomerged using Adobe Photoshop CS3 software (Adobe Systems).…”
Section: Methodsmentioning
confidence: 99%